The determinants of postpartum contraceptive use in Nigeria - Anyatonwu, Obinna Princewill; Nwoku, Kelechi Amy; Jonsson, Håkan; Namatovu, Fredinah (Frontiers in Global Women's Health, 2023)
Introduction: Postpartum contraception is vital for maternal and child health, and reduces the risk of infant mortality. The Health Belief Model (HBM) is a widely accepted framework for exploring health behaviors, such as contraceptive use. Therefore, this study aimed to investigate the factors influencing postpartum contraceptive use in Nigeria and to contextualize the findings within the framework of the HBM.This study was a secondary analysis of cross-sectional data collected from the Demographic Health Survey conducted in Nigeria (NDHS). In total, 28,041 women were included in this study. Self-reported contraceptive use was the outcome, while the explanatory variables included maternal age, place of residence, region of residence, religion, marital status, educational level, household wealth quintiles, knowledge of the ovulatory cycle, decision-maker for health care, and distance to health care facilities. Descriptive statistics and multivariate logistic regression were used to summarize and identify factors influencing postpartum contraceptive use. The HBM was used to discuss the main findings.The prevalence of postpartum contraceptive use in Nigeria is 27%. Our findings showed that the odds of using contraceptives during the postpartum period were higher among women who knew their ovulation cycles, lived in urban areas in the southern region, had no distance barriers to health care, and were 25-49 years old. Education, wealth, and marital status also increase the odds of contraceptive use. However, women who lived in the northeast and northwest regions or shared decision-making with their partners had lower odds.This study highlights the need for region-specific and age-focused interventions to increase contraceptive use in Nigeria. Additionally, increasing accessibility and affordability of contraceptives for younger and economically disadvantaged women, along with promoting women's autonomy in decision-making, can further enhance contraceptive use across Nigeria.